Physical Growth and Sexual Maturation of Subsistence Population in Padaido Island Papua - Insos Batseba Rumayauw; Sita Ratnawati; Elda Irma Jeanne Joice Kawulur (Jurnal Biologi Universitas Andalas, 2024)
Physical growth and sexual maturity are two important events in the childhood phase. Measurement and assessment of development of body size is the best ways to understand the adaptive respond when face enviromental challenges of the traditional population. Several populations show that girls and boys tend to show varying ages and rates of growth and sexual maturity. The aim of this study was to study the growth patterns of height, weight and age at menarche in children of the Biak tribe in the Padaido Islands Region, Biak Regency, Papua Province. Cross-sectional research was designed to the children consisting of 130 boys and 153 girls. In order to determine the age at menarche using the status quo method.  The growth curve was analyzed using the Generalized Linear Model for Location, Shape and Scale (GAMLSS) model and the age of menarche was analyzed using the Probit-GLM analysis. Although geographic condition of Padaido island was isolated, the infrastructure and sosioeconomic conditions were indequate, however the age at menarche of Padaido girls (13,2 years) was included in the same category as the age at menarche nationally. The physical growth curve (height and weight) for girls exceeds that of boys before and during menarche, then decreases after menarche. This pattern is in line with previous research that girls have a larger stature at puberty because they accumulate body fat in preparation for menarche and the development of secondary sex characteristics. The environmental challenges have implications for the limited availability of energy to regulate maximum skeletal growth achieved at a young age, while the development of fat mass is achieved more slowly after sexual maturity. This describes a shift that deviates from the normal growth and development of the body..